Implementasi Model Pembelajaran dalam Pembelajaran Bahasa Arab di MA Sejahtera Pare Kediri - Muhammad Qadhafi; Usman, Soraiya (MUHIBBUL ARABIYAH: Jurnal Pendidikan Bahasa Arab, 2025)
This study aims to identify the instructional models implemented in the teaching of Arabic at Madrasah Aliyah (MA) Sejahtera Pare, Kediri, East Java. The research employs a qualitative approach using descriptive analysis. Data were collected through documentation, observation, and interviews, sourced from both primary and secondary data. Data analysis was carried out through data reduction, data display, and conclusion drawing. The findings indicate that three primary instructional models are commonly used in the Arabic language teaching process at MA Sejahtera: (1) the PAIKEM model, which aims to create an active, creative, and enjoyable learning environment to enhance students' motivation and engagement; (2) the game-based learning model, which serves as an interactive and enjoyable strategy to increase student participation and contextual vocabulary comprehension in Arabic; and (3) the social interaction model, which emphasizes the development of a language-rich environment (bi’ah lughawiyah) and strengthens speaking and listening skills through peer and teacher-student interactions.